Benefits of bifacial solar cells combined with low voltage power grids at high latitudes - Jouttijärvi Sami; Lobaccaro Gabriele; Kamppinen Aleksi; Miettunen Kati (Elsevier Ltd, 2022)
Bifacial photovoltaics (BPV) is a rapidly growing technology that can improve electricity production by utilizing light irradiation from both sides of the panel. A vertical east-west mounting of BPV provides two production peaks, one in the morning and one in the evening, instead of one prominent peak at noon. The vertical mounting of BPV leads to a closer match with typical load profiles and improves the self-consumption of BPV production for household and neighborhood systems. Improving the self-consumption of small-scale PV systems is vital because it increases economic profitability and reduces the requirements for grid interaction. At high latitudes, vertical BPV can be especially beneficial, as the low average solar altitude angle enables the vertical surfaces to efficiently collect irradiation for many hours. This review investigates current state-of-the-art BPV based on modelling and experimental perspectives as well as integrating PV with power grids at different levels. The suitability of BPV in electricity production, its integration to the built environment and landscape and the barriers impeding its implementation are discussed for high latitude conditions. BPV has potential and its application has grown significantly over recent years. However, many key questions have failed to address areas such as the quantitative economic benefits of vertically mounted BPV in terms of the levelized cost of electricity.